Лікування метаболічного синдрому у дітей із застосуванням препарату Гепадиф® - Зелінська, Н. Б.; Бегутова, Т. М. (Clinical Endocrinology and Endocrine Surgery, 2017)
Children with the metabolic syndrome (MS) treatment of must be complex and include a dietary feed, sufficient physical acktivity, setting of metformin and hepatoprotector with an effective complex and metabolic action. The use of Gepadif® in combination with metformin promotes the reliable improvement of BMI, WC, C-peptide, Leptin, lipid profile, blood pressure. For children with MS the TSH level was within the norm limits but was for certain higher, than for healthy children.